ANALISIS PENGARUH CONSUMER INNOVATIVENESS DAN MARKETING MAVEN TERHADAP OPINION LEADERSHIP - willy Arafah (Media Riset Bisnis & Manajemen, 2004)
Consumers term divide in two sections, they are the consumer innovator and "the market maven". The former are eager buyers of new products ; the second are especially knowledgeable about shopping and buying. The present studyexamined the relationship between these two constructs as part of a nomological regression analysis. We used data from 150 consumer of buying new hand phone in Cempaka Mas Mall, Centre of Jakarta to test hypothesized relationship among scores on the market maven scale and a measure ofinnovativeness with opinion leadership. The analysis showed positive correlations among the measure, but there is clear evidence that the consumer innovator and market maven concepts are separate and distinct. The measure of consumer innovativeness predicted the behavioral criteria better than the market maven scale did. Both concepts may be important to manager development as they develop strategies fora new products.